Governmental Indian Policy, Administration, and Economic Planning in the Eastern Subarctic - Hedican, Edward J. (Culture, 1982)
This paper undertakes a comparative analysis of the effects of governmental administration and planning in northern Native communities. The effects are examined with reference to two community types — reserves, with their single-stranded ties to Ottawa’s Department of Indian Affairs, and non-reserve settlements, which have a diversity of outside contacts. It is argued that the limited external contacts characteristic of reserves impede local initiative and foster reliance on decisions made by Government personnel. By contrast, the non-reserve community is able to exercise greater local control because no single external agency is in a position to dominate local affairs. Lacking significant outside structures, leadership in the non-reserve community is able to pursue more autonomous and coherent local planning for economic change.